Ratio of Germination Soybean and Jackfruit’s Seed and Concentration of Fermentation Agent in A Processing of Tempeh - Lely Syefrida Purba; Sentosa Ginting; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The research was perfomed to get the ratio of germination soybean and jackfruit’s seed and fermentation agent concentration in a processing of tempeh. The research had been performed using factorial completely randomized design with two factor i.e : the ratio of germination soybean and jackfruit’s seed (K) : (90:10; 80:20; 70:30; 60:40) and concentration of fermentation agent (R) : (0,2; 0,4; 0,6; 0,8%). Parameters analysed were protein content, fat content, mineral content, water content, and organoleptic values (flavour, taste, and texture). The research showed that ratio of germination soybean and jackfruit’s seed had highly significant effect on protein content, mineral content, water content, and organoleptic values (flavour, taste), and significant effect on organoleptic texture, no significant effect on fat content. The concentration of fermentation agent had highly effect on protein content, fat content, mineral content, water content, and organoleptic values (flavour, taste, texture). The interaction of ratio of germination soybean and jackfruit’s seed and concentration of fermentation agent had highly significant effect on protein content and had no significant effect on fat content, mineral content, water content, and organoleptic values (flavour, taste, texture). The ratio of germination soybean and jackfruit’s seed at 90:10 and 0,8% concentration of fermentation agent produced the best quality of tempeh. Keyword : Tempeh, Germination soybean, Concentration of fermentation agent